Bone age comparison using convolutional neural network - Nawaz, Fariha; Akib, Md. Samiul; Imtiaz, Asif; Ahmad, Sakib Uddin (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.